BƯỚC ĐẦU XÂY DỰNG BỘ MẪU CÁC LOÀI THỰC VẬT KHU BẢO TỒN THIÊN NHIÊN SÔNG THANH, TỈNH QUẢNG NAM - Phạm, Mai Phương; Vũ, Đình Duy; Nguyễn, Vũ Anh; Phan, Kế Lộc; Đặng, Ngọc Huyền; Lê, Xuân Đắc; Nguyễn, Đăng Hội (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
PREPARING THE DRY PLANT SPECIMENS COLLECTION OF SONG THANH NATURAL RESERVE AREA, QUANG NAM PROVINCESong Thanh Nature Reserve (STNR) is located in Nam Giang and Phuoc Son districts, within Quang Nam province along the Vietnam-Laos border, included 93,249 ha of core zone and 108,398 ha of buffer zone. A total of 831 plant species were recognized in 1997 and 1999 by WWF. This study was implemented intend for building the plant specimen, which was operated in the core and buffer zone of Song Thanh Nature Reserve located in La Dee Commune, Nam Giang District. Total of 71 species, belonging to 40 families were represented in specimens; Fam. Rubiaceae and Fam. Euphorbiaceae are considered as the dominant species; Fokienia hodginsii (Dunn) A. Henry & HH Thomas and Helixanthera annamica Danser to be listed among the endangered species in the Vietnam Red Data Book (2007); 10 species of valuable medicinal plants, 3 species of valuable timber, 2 species of fruit trees.